Chemoselective O-acylation of hydroxyamino acids and amino alcohols under acidic reaction conditions: History, scope and applications - Kristensen, Tor E. (Beilstein Journal of Organic Chemistry, 2015)
Amino acids, whether natural, semisynthetic or synthetic, are among the most important and useful chiral building blocks available for organic chemical synthesis. In principle, they can function as inexpensive, chiral and densely functionalized starting materials. On the other hand, the use of amino acid starting materials routinely necessitates protective group chemistry, and in reality, large-scale preparations of even the simplest side-chain derivatives of many amino acids often become annoyingly strenuous due to the necessity of employing protecting groups, on one or more of the amino acid functionalities, during the synthetic sequence. However, in the case of hydroxyamino acids such as hydroxyproline, serine, threonine, tyrosine and 3,4-dihydroxyphenylalanine (DOPA), many O-acyl side-chain derivatives are directly accessible via a particularly expedient and scalable method not commonly applied until recently. Direct acylation of unprotected hydroxyamino acids with acyl halides or carboxylic anhydrides under appropriately acidic reaction conditions renders possible chemoselective O-acylation, furnishing the corresponding side-chain esters directly, on multigram-scale, in a single step, and without chromatographic purification. Assuming a certain degree of stability under acidic reaction conditions, the method is also applicable for a number of related compounds, such as various amino alcohols and the thiol-functional amino acid cysteine. While the basic methodology underlying this approach has been known for decades, it has evolved through recent developments connected to amino acid-derived chiral organocatalysts to become a more widely recognized procedure for large-scale preparation of many useful side-chain derivatives of hydroxyamino acids and related compounds. Such derivatives are useful in peptide chemistry and drug development, as amino acid amphiphiles for asymmetric catalysis, and as amino acid acrylic precursors for preparation of catalytically active macromolecular networks in the form of soluble polymers, crosslinked polymer beads or nanoparticulate systems. The objective of the present review is to increase awareness of the existence and convenience of this methodology, assess its competitiveness compared to newer and more elaborate procedures for chemoselective O-acylation reactions, spur its further development, and finally to chronicle the informative, but poorly documented history of its development.
Keywords: amino alcohols; chemoselectivity; DOPA; hydroxyamino acids; hydroxyproline; O-acylation; organocatalysis; serine; threonine; tyrosine